On the edge-Wiener index of the disjunctive product of simple graphs - Azari, M.; Iranmanesh, A. (Algebra and Discrete Mathematics, 2020)
The edge-Wiener index of a simple connected graph G is defined as the sum of distances between all pairs of edges of G where the distance between two edges in G is the distance between the corresponding vertices in the line graph of G. In this paper, we study the edge-Wiener index under the disjunctive product of graphs and apply our results to compute the edge-Wiener index for the disjunctive product of paths and cycles.